Harmonics Compensation of HAPF with Adaptive Fuzzy Dividing Rule (International Journal of Engineering and Computer Science, 2013)
This paper deals with a hybrid active power filter with injection circuit (IHAPF). It shows great promise in reducing harmonics and improving the power factor with a relatively low capacity active power filter. This paper concluded that the stability of the IHAPF based on detection supply current is superior to that of others. To minimize the capacity of IHAPF, an adaptive fuzzy dividing frequency-control method is proposed by analysing the bode diagram, which consists of two control units: a generalized integrator control unit and fuzzy adjustor unit. The generalized integrator is used for dividing frequency integral control, while fuzzy arithmetic is used for adjusting proportional-integral coefficients timely. And the control method is generally useful and applicable to any other active filters. Compared to other IHAPF control methods, the adaptive fuzzy dividing frequency control shows the advantages of shorter response time and higher control precision. It is implemented in an IHAPF with a 100- kVA APF installed in a copper mill in Northern China. The simulation results implemented, but also very effective in reducing harmonics.